(3QSGdI aj GdJaSjQs - (3CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,TgGH GdOjf, J (B815 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ENJU fHjfG eMeO Udi Gddg Ydjg hSde HcJGH CNQS GdaUMGA hCYLR GdHdZGA s
(3BNQgG (B:s
(3hdPG CSQi Hg Edi hdhW hHgG jJQc YjSi Hf eQje Udi Gddg Ydjg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs